Daily sperm production and testicular morphometry in goats according to external scrotal conformation - Machado Junior, A. A. N.; Assis Neto, A. C. [UNESP]; Sousa Junior, A.; Menezes, D. J. A.; Alves, F. R.; Sousa, A. L.; Carvalho, M. A. M. (Elsevier B.V., 2011)
The present study aimed to compare testicular histology and the testicular cell population as well as spermatogenic efficiency in goats with different scrotal conformations. Eighteen goats were divided into 3 groups: Group I - goats without bipartition of the scrotum, Group II - animals with bipartition of the scrotum up to 50% of the testicular length, Group III - goats with scrotal bipartition more than 50% of the testicular length. In goats in Groups I, II and III, the values for the volume density of seminiferous epithelium were 68.9 +/- 0.6%, 71.5 +/- 2.8% and 73.4 +/- 4.7% (P < 0.05), the height of the seminiferous epithelium were 60.2 +/- 4.9 mu m, 61.0 +/- 5.0 mu m and 73.1 +/- 6.6 mu m (P < 0.05), total length of seminiferous tubules found for Groups I, II and III were 2091.9 +/- 27 m, 2172.5 +/- 24.1 m, and 2340.1 14 m (P < 0.05), number of Sertoli and Leydig cells were 1.8 +/- 0.4 x 10(9) and 1.4 +/- 0.1 x 10(9), 2.2 +/- 0.4 and 2.2 +/- 0.7 x 10(9), and 2.5 +/- 0.1 10(9) and 2.3 +/- 0.510(9)(P < 0.05)and daily sperm production observed were 2.1 0.3 x 109, 2.8 0.4 x 109, and 3.1 0.7 x 109 (P < 0.05). In conclusion, goats with greater scrotal bipartition have a greater capacity to produce reproductive cells that is reflected in a greater reproductive potential. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bipartite scrotum; Histometry; Sperm production; Goat